Psychological Impact of Fake News Among Grade 12 Senior High School HUMSS Students at Bestlink College of the Philippines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study conducted the effects of the Psychological behavior of teenagers on how students react to Fake news. These studies include Humanities and Social Sciences (HUMSS) students in Bestlink College of the Philippines. The purposive sampling process is a total number of 100 students selected to participate in the study. The major instrument that was used for gathering data was a survey questionnaire. The data gathered were analyzed through the use of percentages and weighted mean. Later on, as the researchers investigate that most teenagers use various social media platforms, their social anxiety has increased, affecting their psychological well-being. Therefore, with the rising amount of information on the internet, Fake news has become rampant in today's generation. This study shows the difficulty of increasing the number of teenagers who read fake news. And how teenagers react to what they read on social media sites. Young adults (Teenagers) were the most common victims of this Fake news. As a result, data were presented using descriptive rating data, showing the age and gender of teenagers who read fake news. It implies how rampant Fake news is through social media. Based on such findings and recommendations, local governments must take precautions and be aware of how to differentiate Fake news from real news. Through this paper, researchers can see the real problems mostly experienced nowadays. Attention and guidance were needed for those students who needed a proper understanding.performance. As a result, the study concluded that working from home was more acceptable among BPO employees.